1997
DOI: 10.1515/bchm.1997.378.2.83
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Binding of the Salivary Glycoprotein EP-GP (Identical to GCDFP-15) to Oral and Non-Oral Bacteria Detection and Identification of EP-GP Binding Species

Abstract: Extra Parotid Glycoprotein (EP-GP) is a glycoprotein isolated from human saliva, having homologues in several other body fluids. The biological role of EP-GP and its homologues is unknown. Recently, EP-GP was shown to bind in vitro to the bacterium Streptococcus salivarius HB. In contrast, no binding to a number of other oral microorganisms could be demonstrated. In the present study we have determined whether binding of EP-GP to bacteria occurs in vivo in saliva and in other EP-GP containing body fluids. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 16 publications
(4 reference statements)
0
40
0
Order By: Relevance
“…Furthermore, observation of the bactericidal activity of the 14.2 kDa proteins (Depamede et al, 2012) also strengthens the similarity of these proteins with PIP, since PIP was reported to have affinity to Staphylococcus mutant in human saliva (Ambatipudi et al, 2010). Furthermore, Schenkels et al (1997) also reported that PIP might modulate the colonisation of oral and non-oral bacteria such as those of the genera Streptococcus as well as Gemella, and Staphylococcus hominis isolated from human skin and ear canal. Since the three proteins were observed in Bos taurus as well as in other mammals such as rats, mice, and ovine, it would be interesting to check whether proteins can be used for evolution studies on Bali cattle (Bos sondaicus/javanicus) and ruminants in general.…”
Section: Resultsmentioning
confidence: 88%
“…Furthermore, observation of the bactericidal activity of the 14.2 kDa proteins (Depamede et al, 2012) also strengthens the similarity of these proteins with PIP, since PIP was reported to have affinity to Staphylococcus mutant in human saliva (Ambatipudi et al, 2010). Furthermore, Schenkels et al (1997) also reported that PIP might modulate the colonisation of oral and non-oral bacteria such as those of the genera Streptococcus as well as Gemella, and Staphylococcus hominis isolated from human skin and ear canal. Since the three proteins were observed in Bos taurus as well as in other mammals such as rats, mice, and ovine, it would be interesting to check whether proteins can be used for evolution studies on Bali cattle (Bos sondaicus/javanicus) and ruminants in general.…”
Section: Resultsmentioning
confidence: 88%
“…Its predominance in mucosaltype tissues, as well as its presence in saliva, tears, submucosal glands of the bronchi and apocrine glands of the skin, suggests that PIP may play an important role in mucosal immunity [24]. Schenkels et al [14] used the replica-plate assay to determine the binding of PIP with several bacterial strains in saliva, specifically, Gemella haemolysans, Gemella morbillorium, Streptococcus acidominimus, Streptococcus oralis, Streptococcus salivarius and Streptococcus parasanguis. Similarly, bacteria from the ear canal and skin were identified as Staphylococcus hominis.…”
Section: Inhibition Of Bacterial Growthmentioning
confidence: 99%
“…Moreover, it was postulated that since PIP is capable to bind with hydroxyapatite (a major component of tooth enamel), it may participate in formation of the enamel pellicle [88]. It appears that PIP modulates bacterial colonization because it binds to oral bacteria such as Streptococcus and Gemella [14]. Apart from human, PIP has also been identified and purified in rat saliva [24].…”
Section: Formation Of Enamel Pelliclementioning
confidence: 99%
See 1 more Smart Citation
“…OBP II in the rat shows a 45.5% amino acid identity in a 178 aminoacid overlap with the VEG protein (62). Schenkels et al (63) reported the biochemical characteristics of human lipocalin VEG protein and of extra parotid glycoprotein (EP-GP) isolated with hydroxyapatite-binding assay from the SM and SL glands. EP-GP protein is distributed widely in human tissues in various forms in saliva, sweat, tears, nasal mucus, and seminal fluid.…”
Section: Lipocalinsmentioning
confidence: 99%